21st CENTURY SKILLS IN THE FOREIGN LANGUAGE CLASSROOM: UNIVERSITY STUDENTS’ PERCEPTIONS - P. Valcheva (Trakia Journal of Sciences)
In recent years, the so-called „new literacies”, or 21st century skills, such as critical thinking, creativity, collaboration and communication, have been increasingly developed in the foreign language classroom through the integration of language knowledge, cross-cultural skills and digital competences. These complex perspectives put greater demands on foreign language teachers and learners and raise their awareness of the fundamental changes in the educational setting. PURPOSE: This study seeks to identify university students’ perceptions of the challenges faced by 21st century foreign language teaching and learning. METHODS: A survey among 31 first- and third-year students in Primary School Pedagogy and Foreign Language at St. Cyril and St. Methodius University of Veliko Turnovo was conducted through anonymous pen-to-paper questionnaire in 2022. RESULTS: The results shed light on students’ beliefs, opinions and awareness of the high-order skills that have reshaped the English language classroom in the 21st century. Though students have scarce knowledge on 21st century skills, they are positive about the implementation of these skills in foreign language teaching and learning. CONCLUSION: The paper concludes that there is a pronounced need to raise the students’ awareness as to the potential of the „new literacies” in the foreign language classroom.